Fitofarmaka VALIDITAS DAN RELIABILITAS INSTRUMEN KUESIONER DAN VIDEO EDUKASI PERKEMBANGAN FITOFARMAKA DI INDONESIA: Media Edukasi - Ega Nopita Sari Nopita; Yosef Wijoyo (Universitas Kristen Immanuel, 2022)
Phytopharmaca is a class of natural medicine that has the best level of safety. Research on phytopharmaca is needed to determine the public understanding of phytopharmaca. For this reason, educational videos and questionnaires were developed as a first step to starting intervention and assessment. This research method is research and development (Research and Development), with quantitative and qualitative approaches. Validation of the contents of the questionnaire is carried out by a validator, namely a lecturer who is considered an expert and experienced in the contents of the questionnaire. The results of the content validation test on the questionnaire instrument can already be declared valid by experts (expert judgment) in the fifth round because it has met the valid criteria. The language comprehension test validation was tested on 5 respondents who were considered to meet the same criteria as the research target. The results of the language comprehension test in the first round which was tested on five respondents were declared valid. The reliability test was carried out on 30 respondents who were considered to be able to represent the research target with the Cronbach Alpha value approach. The reliability test can be declared valid or reliable because each variable gets a Cronbach Alpha value > 0.60. Where the value of the knowledge variable is 0.689, the attitude variable is 0.809, and the action variable is 0.702. The validation of educational video in the study was tested on three validators, namely a doctor and two pharmacists. The video validation can be said to be valid because it gets an average validation value of > 3, which is 4.77, which is included in the very valid category. Based on the trial of questionnaires and educational videos on the development of phytopharmaceuticals in Indonesia, it can be declared valid and reliable. So it can be concluded that questionnaires and educational videos can be used as learning media for the development of public knowledge about phytopharmaca in Indonesia.